1984
DOI: 10.4315/0362-028x-47.9.703
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Commercial Depuration of the Sydney Rock Oyster, Crassostrea commercialis

Abstract: Paired batches of unpurified and commercially purified oysters from a polluted estuary were examined for a range of indicator and pathogenic microorganisms on 16 occasions over a period of 1 year. Aerobic plate counts of purified oysters (geometric mean of all samples 4.8 × 102/g) were generally lower than those of unpurified oysters (geometric mean of all samples 1.2 × 103/g). Coliforms and Escherichia coli were detected considerably less frequently, and usually at lower levels in purified than in unpurified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 0 publications
1
20
0
3
Order By: Relevance
“…coli was determined using the conventional five-tube, 3-dilution MPN method [40]. One hundred grams oyster meat sample was homogenized in 100 ml of 0.1% phosphate buffer.…”
Section: Enumeration Of E Coli (Mpn Method)mentioning
confidence: 99%
“…coli was determined using the conventional five-tube, 3-dilution MPN method [40]. One hundred grams oyster meat sample was homogenized in 100 ml of 0.1% phosphate buffer.…”
Section: Enumeration Of E Coli (Mpn Method)mentioning
confidence: 99%
“…3 Os resultados obtidos no presente trabalho, com níveis de contaminação mais altos (10 8 /g, experimento 1) e os demais resultados da Tabela 1, indicam que a dose de 1,0 kGy não foi eficiente para eliminar completamente o microrganismo teste, embora seja eficiente para a eliminação do risco de contrair doença, mesmo em consumidores sensíveis: o nú-mero de células viáveis do V.cholerae diminuiu até ní-veis iguais ou menores que 10 2 /g. Entretanto, é possí-vel a multiplicação dessa bactéria em ostras vivas, antes do consumo.…”
Section: Discussionunclassified
“…Essas medidas incluem: a seleção de área de captura desses organismos (área selecionada de águas livres de contaminação); a depuração após captura; o controle de água e algas que as ostras usam como alimento, seguida de depuração. Uma outra medida preventiva possível para controlar contaminação é o processo de irradiação ionizante, com 60 Co. 3,6,8,[12][13][14]17 Esse processo de intervenção e controle dos agravos à saúde do consumidor tem despertado interesse e se revelado como efetivo na diminuição de riscos microbianos representados pelos perigos como as Salmonella sp, Shigella sp, Escherichia coli O157:H7 e Vibrio cholerae toxigênico, entre outros. 16 Durante a expansão da sétima pandemia de cólera na América Latina e Caribe, o consumo de ostras e pescados crus foi considerado como de alto risco de transmitir essa doença.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Enteric bacteria (e.g., Escherichia coli, fecal coliforms, Salmonella spp.) are eliminated quite effectively (Barrow & Miller 1969, Son & Fleet 1980, Jones et al 1991, whereas viruses (Metcalf et al 1979, Richards 1988, Power & Collins 1989) and indigenous estuarine vibrios (Greenberg et al 1982, Eyles & Davey 1984, Fletcher et al 1991, Jones et al 1991, Tamplin & Capers 1992 are less consistently eliminated. In fact, Tamplin & Capers (1992) reported that Vibrio vulnificus in oysters held at 23°C can persist and replicate at a rate that allows the release of 10 5 bacteria oyster…”
Section: Introductionmentioning
confidence: 99%